Explaining fatigue in ANCA-associated vasculitis - LITTLE, MARK (My University, 2013)
Objectives. To identify the determinants of fatigue among patients with ANCA-associated vasculitis (AAV). Methods. A multicentre cross-sectional study was conducted. Subjects fulfilling the European Medicines Agency criteria for granulomatosis with polyangiitis (Wegener’s), microscopic polyangiitis and eosinophilic granulomatosis with polyangiitis (Churg–Strauss) were approached according to consecutive clinic attendance and invited to complete a questionnaire assessing fatigue and putative biopsychosocial determinants of this symptom. Concurrently, potential clinical determinants were recorded. Independent associations of fatigue were identified using forward stepwise logistic regression modelling and their overall impact expressed as population attributable risk (PAR). Results. The majority (74.8%) of participants (n = 410) reported high levels of fatigue that were found to be significantly associated with numerous biopsychosocial and clinical factors. Sleep disturbance [odds ratio (OR) 5.3, 95% CI 2.7, 10.5] and pain (OR 3.8, 95% CI 2.0, 7.3) were the strongest independent associations of fatigue and, on a population level, each was more than twice as important as any other putative determinant (PAR 18.1% and 16.5%, respectively). Female gender (OR 2.1, 95% 1.1, 4.0), elevated CRP (OR 3.7, 95% CI 1.7, 8.1) and the dysfunctional coping strategies of behavioural disengagement (OR 2.4, 95% CI 1.04, 5.6) and denial (OR 2.4, 95% CI 0.9, 6.7) were also independently associated with fatigue. Conclusion. The data suggest that AAV-related fatigue is multifactorial in origin. Sleep disturbance and pain were found to be most important, although inflammation, as measured by CRP, was also associated. This study has identified potentially modifiable determinants that will inform future interventions aimed at alleviating fatigue.
PUBLISHED
Keywords: fatigue ANCA-associated vasculitis granulomatosis with polyangiitis microscopic polyangiitis eosinophilic granulomatosis with polyangiitis; fatigue ANCA-associated vasculitis granulomatosis with polyangiitis microscopic polyangiitis eosinophilic granulomatosis with polyangiitis